GOLONGAN PUTIH DALAM PELAKSANAAN PEMILIHAN KEPALA DAERAH PROVINSI RIAU DI DESA BATURIJAL HULU KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU TAHUN 2013 - Herdi Fadillah; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
The research present describe the golput in Governor and Vice of Governor election in Baturijal Hulu Village Riau Province in 2013. Phenomenon of golput nowdays have influence in election of chief District Riau Province. Like phenomenon of golput in Baturijal Hulu Village with 1.266 electors, but only 331 electors that use election right with percentace golput arround 72%. It is influence with participation of society to vote of Governor and vice of Governor.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Baturijal Hulu Village Indragiri Hulu Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Karimun Head of District Baturijal Village and society in Baturijal Village.The conclution of this research are implementation of Governor and vice of Governor election in Baturijal Hulu village peranap District in 2013 has high of golput scale. It caused by some factors like: apatisme society of elector in Baturijal Hulu village that think about vote or not it’s not give influence for them. And also the elector that does not in the village at the votes day.Keywords: Golput, election and Governor, Vice of Governor.